Relationship between family support with cognitive function and quality of life in the elderly - Idris, Desi Natalia Trijayanti; Taviyanda, Dian; Pattipeilohy, Kerenhapukh (Riset Informasi Kesehatan, 2025)
Background: Elderly people often experience problems related to their cognitive function that will interfere with their quality of life; therefore, family support is needed for the elderly. The purpose of this study was to analyze the relationship between family support and cognitive function and quality of life of the elderly in RW 02, Bangsal Village, Kediri City. Method: Research Design correlation with cross-sectional. Independent variables with family support and dependent variables are cognitive function and quality of life. The elderly population in RW 2 Bangsal Village was taken using a purposive sampling technique by producing a sample of 62 respondents. The measuring instrument used a questionnaire, namely family support, cognitive function using the MMSE questionnaire, and the quality of life of the elderly using the OPQOL Brief questionnaire. Data analysis using the Spearman rho statistical test and the ANOVA test. Results: The results of the study showed that most elderly people had good family support, as many as 49 (79%). Elderly people experienced cognitive dysfunction with a percentage of moderate cognitive impairment as many as 18 (33.9%) and severe cognitive impairment as many as 22 (30.6%). Most elderly people had a good quality of life, which was as many as 53 (85.1%). The results of statistical tests for the relationship between family support and cognitive function showed p = 0.019 with a correlation coefficient of 0.298, and the results of statistical tests for the relationship between family support and quality of life showed p = 0.001 with a correlation coefficient of 0.402. In the ANOVA test, p = 0.042 was obtained for cognitive function; in quality of life, the data was not homogeneous. Conclusion: There is a relationship between family support and cognitive function and also quality of life in the elderly at the Elderly Posyandu RW 02, Bangsal Village, Pesantren District, Kediri City. When the family provides support, there will be a difference in cognitive function and quality of life in the elderly. The better the family support, the less likely the elderly will enter cognitive disorders and the better quality of life they will have.